2017
DOI: 10.1007/s11604-017-0711-2
|View full text |Cite
|
Sign up to set email alerts
|

HRCT texture analysis for pure or part-solid ground-glass nodules: distinguishability of adenocarcinoma in situ or minimally invasive adenocarcinoma from invasive adenocarcinoma

Abstract: The 90th percentile CT numbers and entropy can accurately distinguish AIS-MIA from IAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…However, the majority of the studies were performed with slice thickness comparable to the American College of Radiology (ACR) LDCT protocol recommendations for lung cancer screening and the comparison of patient characteristics and acquisition parameters did not reveal significant differences between SSN classes 10,11 . The overall number of nodules is relatively small but comparable and larger than many other studies 1416,21,22,24,26,27 . Predictive classification performance was thus established in a limited number of cases for both training and testing.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…However, the majority of the studies were performed with slice thickness comparable to the American College of Radiology (ACR) LDCT protocol recommendations for lung cancer screening and the comparison of patient characteristics and acquisition parameters did not reveal significant differences between SSN classes 10,11 . The overall number of nodules is relatively small but comparable and larger than many other studies 1416,21,22,24,26,27 . Predictive classification performance was thus established in a limited number of cases for both training and testing.…”
Section: Discussionmentioning
confidence: 44%
“…Yagi T et al . reported that the 90 th percentile together with entropy were independent differentiators of PIA from AIS-MIA with an area under the curve 0.90 24 . Using radiomics with 57 morphologic and texture-based features and Support Vector Machines (SVM), Li M et al .…”
Section: Discussionmentioning
confidence: 98%
“…Chen et al picked 76 features meaningful for the distinction of malignancy of pulmonary nodules from 750 extracted radiomic features and built a predictive model whose accuracy was up to 84% using four selected advanced features ( 20 ). Yagi et al carried out the texture analysis of high-resolution computed tomography (HRCT) and found that 90th percentile and entropy performed well in discrimination between AIS/MIA and IVA with an AUC value of 0.90 (95% CI: 0.84–0.95) ( 13 ). Three different predictive models set with clinical, radiological, and nine selected radiomic features from 960 features extracted from unenhanced CT images in our study all presented good predictive power in the discrimination between AIS/MIA (indolent adenocarcinoma) and IVA (AUC > 0.8, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with IVA, AIS, and MIA are considered as indolent lung adenocarcinoma because of the excellent prognosis ( 11 , 12 ). AIS/MIA could be followed up or treated with sublobar resection while more aggressive surgical interventions should be taken for IVA ( 13 , 14 ). Several previous studies revealed that the 5-year survival rates of AIS and MIA could be 100% and near 100% with a complete resection while that of IVA in stage Ia is no more than 75% ( 11 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation